Investigation on varied sewage sludge producer gas and methane blend equivalence ratios operated SI engine intact with Miller cycle strategy - Jena P.; Tirkey J.V.; Raj R.; Prajapati L.K. (My University, 2025)
Decentralised power generation through a gasifier-engine genset can reduce both reliance on power grid and pollution. However, the low calorific value of the produced gaseous fuel moderates engine power and efficiency, which is a big challenge for its utilisation. For early and cost-effective solution prediction, a simulation tool of adequate precision can effectively envisage dual-fuel (DF) mode engine performance. Thus, this study simulates DF-SI engines with late inlet valve closures (LIVCs) to improve thermal efficiency using the Miller cycle strategy. Simulation is performed using quasi-dimensional thermodynamic modelling (QDTM). After validating the model using referred experimental results, QDTM was employed to study the parametric impacts of inputs (blends, LIVC and equivalence ratio) variations on performance and emissions response parameters. Power improves by blending sewage sludge-based producer gas with methane. Multi-objective optimisation through the response surface method (RSM) determined the optimum operating parameters as 0.814 equivalence ratio, 68.23% SSPG-blend and 55.9° CA (ABDC) LIVC. Corresponding optimal responses were 5.906 bar IMEP, 3.85 kW BP, 28.6% BTE, 12.596 MJ/kWh BSEC, 0.134 V% CO and 2045.29 ppm NO emissions. ANOVA-based optimal results presented a composite desirability of 0.843 with a 95% confidence level. Conclusively, methane mix and LIVC approach increase the power and efficiency of the DF-SI engine; additionally, optimisation guides to balance power and emission trade-off. © 2024 Informa UK Limited, trading as Taylor & Francis Group.